Nitric Oxide Is Essential for Melatonin to Enhance Nitrate Tolerance of Cucumber Seedlings - Yiting Zhang; Ailong Liu; Yanwei Hao; Wei Su; Guangwen Sun; Shiwei Song; Houcheng Liu; Riyuan Chen (Molecules, 2022)
Melatonin (MT) and nitric oxide (NO) in plants can function cooperatively to alleviate salt stress, sodic alkaline stress and immune response, as well as adventitious root formation. The interaction of MT and NO on the nitrate stress tolerance of cucumber seedlings are not well understood. We investigated the effects of exogenous MT, NO donor (SNP) and NO scavenger (cPTIO) on the growth; photosynthesis; characteristics of root morphological; accumulation of mineral elements, endogenous NO, MT, IAA and ABA; and related genes expression in cucumber (Cucumis sativus L. “Jin You No. 1”) seedlings grown under high nitrate condition (HN). The results showed that MT and NO independently alleviated the inhibition of growth and photosynthesis capacity of cucumber seedlings under nitrate stress. NO was required for MT to enhance the root activity, root length, lateral root number and the accumulation of calcium, magnesium and iron in the roots of cucumber seedlings grown under nitrate stress. Consistently, the expression of adventitious rootless 1 gene (CsARL1) was modulated. Furthermore, exogenous MT induced accumulation of endogenous MT, NO, indole-3-acetic acid (IAA) and abscisic acid (ABA), mainly within 24 h after treatment, in which MT and NO were further increased at 48 h and 96 h, IAA and ABA were further increased at 16 h in the presence of SNP. In contrast, the accumulation of endogenous IAA, MT and ABA slightly decreased within 24 h, NO significantly decreased at 192 h in the presence of cPTIO. Correspondingly, the expression levels of genes involved in nitrogen metabolism (CsNR1 and CsNR2), MT metabolism (CsT5H, CsSNAT2 and Cs2-ODD33), auxin carriers and response factors (CsAUX1, CsGH3.5, CsARF17), ABA synthesis and catabolism (CsNCED1, CsNCED3 and CsCYP707A1) were upregulated by MT, in which CsNR1, CsNR2, CsAUX1, CsNCED3 and CsT5H were further induced in the presence of SNP in roots of cucumber seedlings. These observations indicated that NO act as a crucial factor in MT, alleviating nitrate stress through regulating the mechanism of root growth in cucumber seedlings.